2000
DOI: 10.1002/1097-0320(20000901)41:1<55::aid-cyto8>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of cell permeabilization for multiparametric flow cytometric analysis with lectin staining

Abstract: Background This study was undertaken in mice to develop a reproducible procedure of cell permeabilization, allowing intracellular protein staining by immunofluorescence (i.e., Bcl‐2) without losing surface labeling especially for lectins (i.e., B220 and peanut agglutinin [PNA]). This article reports results obtained with different permeabilization protocols. Methods Lymphoid cells were extracted and prepared from Peyer's patches and spleen. After surface labeling using anti‐B220‐Cy‐chrome and PNA‐biotin/strept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…For these reasons we examined the presence of retinoschisin inside and outside photoreceptor, bipolar, and Müller cells by immunostaining dissociated cells that had or had not been permeabilized with methanol. This treatment has been shown to remove some proteins local-ized to the cell surface [i.e., the lectin peanut agglutinin (Verdier et al, 2000)] and to allow the detection of intracellular proteins Schipper et al, 1999). Consistent with these observations, we found that immunofluorescent staining of the cell-surface protein ROB was substantially reduced by methanol permeabilization (data not shown) and that intracellular CRALBP could be detected after methanol treatment.…”
Section: Retinoschisin In Dissociated Retinal Cellssupporting
confidence: 82%
“…For these reasons we examined the presence of retinoschisin inside and outside photoreceptor, bipolar, and Müller cells by immunostaining dissociated cells that had or had not been permeabilized with methanol. This treatment has been shown to remove some proteins local-ized to the cell surface [i.e., the lectin peanut agglutinin (Verdier et al, 2000)] and to allow the detection of intracellular proteins Schipper et al, 1999). Consistent with these observations, we found that immunofluorescent staining of the cell-surface protein ROB was substantially reduced by methanol permeabilization (data not shown) and that intracellular CRALBP could be detected after methanol treatment.…”
Section: Retinoschisin In Dissociated Retinal Cellssupporting
confidence: 82%
“…We avoided the use of intracellular staining here because permeabilization conditions have been shown to critically affect results in both B cells (Verdier et al, 2000) and T cells (Papagno et al, 2007), suggesting that optimization of intracellular flow cytometry protocols for microglia/macrophages will not be trivial. Additional benefits of limiting the protocol to surface stains are the retained ability to sort live cells for functional experiments, as well as a significant reduction in time and labor.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of Bcl-2 content was assessed on B-cells, after a fixation/permeabilization step that we performed with a commercial kit (Intrastain, Dako, Trappes, France) previously tested in our laboratory (20). Permeabilization was undertaken simultaneously with hamster anti-mouse Bcl-2-uncoupled monoclonal antibody (Pharmingen, 1 lg/10 6 cells) for 15 min at room temperature in the dark.…”
Section: Dna Cell Content Enriched 10mentioning
confidence: 99%